'Public–Private Entanglement': Entrepreneurship in Lebanon's Hybrid Political Order. Issue 2 (1st February 2016) - Stel, Nora; Naudé, Wim
Abstract: While the literature is clear that political influence and clientelism characterises the investment decisions of entrepreneurs and the performance of their firms when governance is weak, it is less understood how governance systems and entrepreneurs interact, particularly when governance is of a hybrid nature. We address this issue in this paper by studying how entrepreneurs obtain access to electricity in Lebanon, showing that the hybrid political order imposes a high cost on electricity. We furthermore find that a hybrid political order channels entrepreneurial talent into lobbying and bribery. The key constraint that emerges from the hybrid political order in this case is the corrupt organisation of governance of the electricity sector. This results in higher prices (because bribes for contracts have to be earned back) in entrenchment of oligopolies, because contracts often come with political protection.